Exploration of the gap between business management curriculum and employability requirements: a study of curriculum designers and recruiters’ perceptions - Hum Chan; Abdul Aziz Ab Latif; Yohan Kurniawan (2012)
This paper explores the perceptions of curriculum designers and recruiters toward factors creating the gap between business management curriculum at university and employability requirements of banking industry in Cambodia. Qualitative paradigm with a specific design of exploratory case study was employed. Documents, observations and structure interviews with 6 respondents (2 curriculum designers, 4 recruiters) were used, and a direct analysis was applied. Data analysis was classified into categories (1) perception of curriculum designers and (2) perception of recruiters. Based on the case data, the study identified four main factors (1) loose enforcement of educational policy and law on nurturing relationship between university and industry in developing curriculum, (2) misperception among university and industry toward skills development in the curriculum, (3) scarcity of resources in implementing business management curriculum, and (4) information gap between university and industry to develop and update business management curriculum. With these evidences, several implications and suggestions have been made to government, line ministries, universities, industries and students for further study of business management curriculum and its challenges to design compatible curriculum that meet national, regional and global skill standards.